The dual role of neutrophil extracellular traps (NETs) in sepsis and ischemia-reperfusion injury: comparative analysis across murine models - Kiwit, Antonia; Lu, Yuqing; Lenz, Moritz; Knopf, Jasmin; Mohr, Christoph; Ledermann, Yannick; Klinke Petrowsky, Michaela; Pagerols Raluy, Laia; Reinshagen, Konrad; Herrmann, Martin; Boettcher, Michael; Elrod, Julia (International journal of molecular sciences, 2024)
A better understanding of the function of neutrophil extracellular traps (NETs) may facilitate the development of interventions for sepsis. The study aims to investigate the formation and degradation of NETs in three murine sepsis models and to analyze the production of reactive oxygen species (ROS) during NET formation. Murine sepsis was induced by midgut volvulus (720° for 15 min), cecal ligation and puncture (CLP), or the application of lipopolysaccharide (LPS) (10 mg/kg body weight i.p.). NET formation and degradation was modulated using mice that were genetically deficient for peptidyl arginine deiminase-4 (PAD4-KO) or DNase1 and 1L3 (DNase1/1L3-DKO). After 48 h, mice were killed. Plasma levels of circulating free DNA (cfDNA) and neutrophil elastase (NE) were quantified to assess NET formation and degradation. Plasma deoxyribonuclease1 (DNase1) protein levels, as well as tissue malondialdehyde (MDA) activity and glutathione peroxidase (GPx) activity, were quantified. DNase1 and DNase1L3 in liver, intestine, spleen, and lung tissues were assessed. The applied sepsis models resulted in a simultaneous increase in NET formation and oxidative stress. NET formation and survival differed in the three models. In contrast to LPS and Volvulus, CLP-induced sepsis showed a decreased and increased 48 h survival in PAD4-KO and DNase1/1L3-DKO mice, when compared to WT mice, respectively. PAD4-KO mice showed decreased formation of NETs and ROS, while DNase1/1L3-DKO mice with impaired NET degradation accumulated ROS and chronicled the septic state. The findings indicate a dual role for NET formation and degradation in sepsis and ischemia-reperfusion (I/R) injury: NETs seem to exhibit a protective capacity in certain sepsis paradigms (CLP model), whereas, collectively, they seem to contribute adversely to scenarios where sepsis is combined with ischemia-reperfusion (volvulus).
Online veröffentlicht: 28. März 2024
Gesehen am 23.07.2024